2006
DOI: 10.1016/j.chemosphere.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of earthworms (Eisenia fetida) on the fractionation and bioavailability of rare earth elements in nine Chinese soils

Abstract: The effect of earthworm (Eisenia fetida) activity on soil pH, dissolved organic carbon (DOC), fraction distribution pattern and bioavailability of rare earth elements (REEs) Y, La, Ce, Pr and Nd in nine Chinese soils were investigated using pot experiments. A three-step extraction procedure recommended by the European Community (Standards, Measurements and Testing Programme) was used to fractionate REEs in soils into water soluble, exchangeable and carbonate bound (B1), Fe-and Mn-oxides bound (B2) and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 34 publications
2
24
2
Order By: Relevance
“…In this study, it was found that the presence or absence of organisms (earthworms and plants) did not change the pH values. Our results are however inconsistent with most previous studies, which have shown that, in contaminated soils earthworm activity increased soil pH (Wen et al, 2006;Udovic and Lesta, 2007). The mechanisms by which E. fetida should change pH value are still unclear (Sizmur and Hodson, 2009).…”
Section: Effects Of Earthworms and Plants On The Ph And The Availabilcontrasting
confidence: 57%
“…In this study, it was found that the presence or absence of organisms (earthworms and plants) did not change the pH values. Our results are however inconsistent with most previous studies, which have shown that, in contaminated soils earthworm activity increased soil pH (Wen et al, 2006;Udovic and Lesta, 2007). The mechanisms by which E. fetida should change pH value are still unclear (Sizmur and Hodson, 2009).…”
Section: Effects Of Earthworms and Plants On The Ph And The Availabilcontrasting
confidence: 57%
“…Earthworms have been shown to affect soil physical properties, such as density, structure, aeration, and moisture (Jordan et al 1999Ponder et al 2000). Chemical properties, such as pH, nutrient availability, and heavy metals are affected by earthworms (Buse 1990;Robinson et al 1992;Buck et al 1999;Wen et al 2006). Earthworms influence microbial composition, biomass, and activity and thus affect the rates and patterns of mineralization and immobilization in soils (Bohlen and Edwards 1995;Binet and Trehen 1992;Binet et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the values of contaminated soil pH in the presence of earthworm increased from 0.16 to 2.06 units. Similarly Wen, et al [47] have found that soil pH increased from 0.2 to 1.1 due to earthworm (Eisenia fetida) activity. This noticeable increase in soil pH by earthworm has been attributed to the granules of calcium carbonate produced by the calciferous glands located into the earthworm esophagus [51].…”
Section: Total and Bioaccessible Bi In Soilmentioning
confidence: 99%
“…This was possibly caused by a stronger affinity of Bi to form chelating complexes with metallophores and other biomolecule produced by earthworm. On the other hand, some studies suggested that the earthworms could stimulate the growth of soil bacterial populations that enzymatically degrade soil organic matter causing the release of the organically bound metal [45][46][47]. Bi bioaccessibility increased significantly following the death of the earthworms.…”
Section: Total and Bioaccessible Bi In Soilmentioning
confidence: 99%